Correlation of Lifestyle with Physical Fitness in Sports Students Based on Gender - Syfani Fadilah; Didin Budiman; Wildan Alfia Nugroho (Universitas Negeri Semarang, 2025)
This study aims to examine the relationship between lifestyle and physical fitness in sports students of the Physical Education Study Program for Elementary School Teachers at University Of Education Indonesia, based on gender. Using a quantitative approach with a descriptive correlational and cross-sectional design, this research involved 90 purposively selected students (54 male and 36 female). Data were collected using the Health Promoting Lifestyle Profile II (HPLP-II) questionnaire to measure lifestyle and the Indonesian Physical Fitness Test (TKJI) to assess physical fitness. The results of the Spearman’s rho correlation analysis showed a very strong and significant relationship between lifestyle and physical fitness (r = 0.989; p < 0.001). Students with a healthier lifestyle tended to have better physical fitness scores. Interestingly, no substantial differences were found between male and female students in both lifestyle and fitness levels. These findings underscore the crucial role of lifestyle in shaping physical fitness and suggest that gender-inclusive health education and campus-based support are essential.